Monitoring inclusive urban development alongside a human rights approach on participation opportunities. Issue 5 (3rd May 2020) - Eckhardt, Jennifer; Kaletka, Christoph; Pelka, Bastian
ABSTRACT: Visions of a society for all are closely intertwined with the question of how to develop inclusive communities. Social innovations are able to facilitate inclusion and catalyse the improvement of participation opportunities, especially in urban settings, as this is the place where positive and negative transformation becomes noticeable first. New legislation on international, national, as well as on regional and communal levels has set new goals and standards regarding social inclusion in urban structures, and monitoring and reporting efforts will show whether these requirements are met or not. In recent years, social monitoring and reporting systems have evolved and gained a human rights-based perspective by denoting the actual life-situation of people affected. On the basis of the human rights approach to participation, Germany started to reconfigure its reporting system. First municipalities have started to implement it. This Paper reflects on two different approaches to implement the new federal reporting system on a local level. Based on a generic context-understanding guide of innovative processes, collaborative municipal reporting is analysed as a social innovation itself. It especially tries to single out the benefits collaborative and interdisciplinary modes of work may hold for city administrations in the field of social reporting efforts.